MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK MELALUI KEGIATAN MENGANYAM MENGGUNAKAN KERTAS PADA ANAK USIA 5-6 TAHUN DI PAUD ARRASYID ARRASYID TAHUN PELAJARAN 2023/2024 - Khairul Huda; Rahman (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
Improving Children's Fine Motor Skills Through Weaving Activities Using Paper for Children Aged 5-6 Years at PAUD Arrasyid Academic Year 2023/2024. The aim of this research is to determine the extent to which children's fine motor skills improve through chicken activities at Arrasyid PAUD. The results of the research and discussions that have been carried out can be concluded that learning through weaving activities using paper can improve children's fine motor skills at PAUD Arrasyid Arrasyid for the 2023/2024 academic year. This is shown by the increase in children's fine motor skills, namely from the initial condition that there were 6 children who had not yet developed or 37.5%, in cycle I there were 4 children or 25%, in cycle II there were none who had not developed. In the initial condition the number of children who began to develop was 8 people or 50%, in cycle I there were 5 children or 31.25%, in cycle II there were 2 children or 12.5% who began to develop, for the children to develop according to expectations in the initial condition as many as 2 children or 12.5%, in cycle I there were 6 children or 37.5%, in cycle II there were 9 children or 56.25%, while the children developed very well in the initial condition there were none, in cycle I as many as 1 child or 6.25% and in cycle II there were 5 children or 31.25%.